Supporting parents in facilitating computational thinking for young children through loose parts construction play - Cynthia Ai Ming Lim; G Kaveri; Jiayao Li; Mian Yee Choy (Future in Educational Research)
Abstract Computational thinking (CT) as an essential problem‐solving and thinking skill for all students has been the focus of much interest from education systems all over the world (Chen et al., 2023). Unplugged activities like constructing and play with loose parts provide a low‐cost solution to naturally weave in learning of CT skills for young children at home and formal learning environments. Such activities provide opportunities particularly for children from economically disadvantaged backgrounds to access learning of CT skills so they will not be left behind. This article describes the pilot study of a programme that introduced an open‐ended construction play activity using loose‐parts to parent–child dyads from economically disadvantaged backgrounds, with the aim to support parents in facilitating play interactions in ways to promote CT skills for their children using question cards. The cards contained questions that parents could use to foster CT skills like decomposition and algorithmic thinking in their play interactions. Focus group discussions were held before and after the play sessions and parents in the study reported more confidence in supporting their children in play and learning of 21st century skills of teamwork, collaboration and CT skills. The results demonstrate the potential of unplugged pedagogy for promoting CT skills for young children especially in the home environment through engagement with families, with implications for home–school collaborative learning environments and parent education. Recommendations for practice and research are provided accordingly.